0.03 V Electrolysis Voltage Driven Hydrazine Assisted Hydrogen Generation on NiCo phosphide Nanowires Supported NiCoHydroxide Nanosheets. Issue 14 (28th July 2020) - Li, Mujie; Zhang, Zhongyi; Xiong, Hailang; Wang, Linan; Zhuang, Shuxian; Argyle, Morris D.; Tang, Yang; Yang, Xiaojin; Chen, Yongmei; Wan, Pingyu; Fan, Maohong
Abstract: In order to decrease the electricity consumption of hydrogen generation, hydrazine‐assisted water electrolysis is intensively investigated recently. Herein, hierarchical nanostructure of ultrathin NiCo(OH) x nanosheets (NSs) that in‐situ grown on the NiCoP nanowires (NWs) was deposited on nickel foam (NF) to construct NiCo(OH) x @NiCoP/NF electrode. NiCoP NWs extend the surface area, spatial utilization of NF and enhance the electron conduction to the outmost NiCo(OH) x NSs. NiCo(OH)x NSs interlace to form regular mesoporous channels, which improve the structural stability and mass transfer rate. Moreover, NiCoP NWs enhance the adsorption of protons and the transfer of electrons, while NiCo(OH) x NSs facilitate the adsorption of OHad during reaction. As a result, NiCo(OH) x @NiCoP/NF exhibits excellent activity for both hydrazine oxidation reaction (HzOR) and hydrogen evolution reaction (HER). Based on the NiCo(OH) x @NiCoP/NF||NiCo(OH) x @NiCoP/NF couples, electrolysis of hydrazine for hydrogen generation only requires an extremely low cell voltage of 0.03 V. Abstract : Assisted evolution : Hierarchical self‐supported NiCo(OH) x @NiCoP/NF electrode exhibits outstanding bifunctional activity toward both hydrazine oxidation reaction (HzOR) and hydrogen evolution reaction (HER). The electrolysis of hydrazine (N2 H4 ) for producing hydrogen consumes an extremely low cell voltage of 0.03 V, which is less than 2 % of the traditional water electrolysis (1.54 V) based on precious Pt and RuO x electrocatalysts.